Naissance et dynamique de la nouvelle pensée économique bolivienne - Diego Landivar (Revue de la Régulation)
With actual Financial crisis, economists’ work has been criticized by civil society. This article tries to explore the conditions and limits that lead to independent economic thoughts in relation to standard models. The case of new Bolivian economic thought is used here to illustrate that question. Our analysis combines historical, sociological and theoretical dimensions, which leads to a better understanding of the question.The last part of this article is based on a reflection about tensions and attracting forces that may lead new intellectual models to be vulnerable and even more, inconsistent.